51.5k views
1 vote
This equation has one solution.

3(x – 2) + 4x = 10(x + 1)

What is the solution?

2 Answers

3 votes

Answer:

-16/3

Explanation:

:) :) :) :)

User RobinL
by
4.8k points
3 votes

Answer:
x=-(16)/(3)

Explanation:

You must solve for x, as following:

- Apply the distributive property:


3x-6+4x=10x+10

- Add the like terms:


3x+4x-10x=10+6


-3x=16

- Divide both sides of the equation by -3, as following:


(-3x)/(-3)=(16)/(-3)

Then the solution is:


x=-(16)/(3)

User Daddy
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.